The use of social networks in the management of transnational corporate communication: An analysis conducted on the administrative staff of the Universidad Técnica Particular de Loja in Ecuador, Spain, USA, and Italy [El Uso De Las Redes Sociales En La Gestión De La Comunicación Corporativa Transnacional Análisis de la Universidad Técnica Particular de Loja en Ecuador, España, Estados Unidos e Italia] - Aguilar Campoverde, B. (2016)
The recent introduction of social networks has revolutionized the communication between people and corporations. Social networks have also a key role due to numerous benefits that these platforms offer in the field of business management. The purpose of the present study is to determine the effects of using social networks on managing corporate communication at the Universidad Técnica Particular de Loja. The participants were the administrative staff members of this institution. The results show that 80% of the staff uses social networks in the management of corporate communication, mainly to do activities related to work (91%), and as a means of communication (69%).